Modern Theories of Regional Development – a Review of Some Concepts - Bogdański, Marcin (Oeconomia Copernicana, 2012)
Researches on determinants of regional development are an important part of economic thought. And just like the whole economic theory, it was the subject of visible evolution as the whole economy had changed and as we gained some practice in stimulating economic development. However, in the public awareness one can still observe a strong influence of “old” or traditional theories. Many (also some economists) still see regional development as an exogenous process which should be inspired and managed by a central government. Also, there is a strong tendency to consider the main goal of regional policy as artificial leveling of regions’ development. Only recently there has been a visible shift in the approach to the problem of regional development. The aim of the article is to present some most commonly recognized modern theories of regional development, which stand opposite to the traditional approach. It shows the evolution of theories of regional development from exogenous to endogenous concepts, and from the sectoral to holistic view on this issue. Of course, it does not cover all of the thoughts of a fruitful discussion on this topic. It is rather an inspiration to increase and improve one’s knowledge of this topic.